Effects of stress on conductivity insulators - Хейрабади, Газаля Сабир кызы (Technology audit and production reserves, 2012)
In article influence of a tension on the electric resistance of polymeric materials is studied. Analytical expression for resistance depending on mechanical and rheological properties polymers, from a tension and time is received